Burnout in elite rugby: Relationships with basic psychological needs fulfilment - Hodge, K.; Lonsdale, C.; Ng, J. Y. Y. (Journal of Sports Sciences, 2008)
In this study, we examined the utility of self-determination theory (Ryan & Deci, 2002) as a framework for understanding the antecedents of athlete burnout in elite New Zealand rugby union players (n=133). Perceptions of competence, autonomy, and relatedness (i.e. basic psychological needs) were hypothesized to be negatively related to burnout scores, while players classified as "high-burnouts" were predicted to report lower needs fulfilment than players with low burnout. Canonical correlation analysis indicated that relatedness was a low to moderate predictor of burnout, but players' competence and autonomy accounted for substantial portions of variance in two athlete burnout symptoms: reduced accomplishment and sport devaluation. The proportion of variance accounted for in the exhaustion dimension of athlete burnout was not substantive. Multivariate analysis of variance supported these results, as "high-burnout" players had lower competence and autonomy scores than athletes reporting low burnout symptoms. The two groups did not report significantly different relatedness scores. Implications of these results for researchers and practitioners are discussed.